2020
DOI: 10.1080/23743603.2020.1756239
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the consistency and value of humour style profiles

Abstract: Establishing generalisable humour style profiles promises to have significant value for educational, clinical, and occupational application. However, previous research investigating such profiles has thus far presented inconsistent results. To determine the generalisability and value of humour style profiles, a large and geographically diverse examination of humour styles was conducted through a cross-sectional questionnaire methodology involving 863 participants from across three world regions. Findings ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…In conclusion, Study 1 confirmed that the examination of humor types enables a more comprehensive insight into the common core of humor style profiles and allows for a more precise understanding of associations with personality and possible neural processes underlying personality traits. The identified clusters of humor found correspond to the findings from Galloway (2010), Leist and Müller (2013), and Evans et al (2020), supporting the stability of humor types generated from humor styles. In addition, the number of identified humor types is closely linked with the criterion of selection within the cluster analysis.…”
Section: 3supporting
confidence: 81%
See 1 more Smart Citation
“…In conclusion, Study 1 confirmed that the examination of humor types enables a more comprehensive insight into the common core of humor style profiles and allows for a more precise understanding of associations with personality and possible neural processes underlying personality traits. The identified clusters of humor found correspond to the findings from Galloway (2010), Leist and Müller (2013), and Evans et al (2020), supporting the stability of humor types generated from humor styles. In addition, the number of identified humor types is closely linked with the criterion of selection within the cluster analysis.…”
Section: 3supporting
confidence: 81%
“…Investigating humor types, as patterns of humor styles, allows better insight into the nature of humor. Studies that analyze clusters of humor styles show some similarities in results, but not all the clusters are replicated ( Evans et al, 2020 ). Certain types of humor emerged consistently, while some are confirmed only within specific contexts ( Evans & Steptoe-Warren, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the variable-oriented examination of the effects of humor styles has recently been characterized as reductionist, and it has been recommended that effects of humor styles should be complemented by person-oriented approaches that analyze typical humor style configurations (i.e., profiles of concurrent humor styles use) rather than single humor styles [ 48 ]. For example, individuals scoring high on self-defeating humor and low on the other three humor styles were identified to have the lowest score of psychological adjustment compared to other humor style profiles [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, individuals scoring high on self-defeating humor and low on the other three humor styles were identified to have the lowest score of psychological adjustment compared to other humor style profiles [ 23 ]. When directly compared with humor styles, humor profiles were shown to have consistently greater predictive value for friendship and well-being outcomes [ 48 ]. Therefore, in addition to the variable-oriented analyses of individual humor styles (in the form of mediation and moderation models), the current study will also examine person-oriented differences between latent profiles of combined humor style use.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have written on the role of humour in health care for instance in palliative care (32, 33) and more explicitly in higher education (34,35). Jones (4) helpfully adapted Dean and Gregory (32) cautions and guidelines on the use of humour which is presented in Fig.…”
Section: Discussionmentioning
confidence: 99%